Convivialist multilingual education: theoretical and practical suggestions from a Norwegian perspective - Brossard Børhaug, Frédérique; Manral, Mallika (Frontiers in Education, 2024)
The article aims at exploring the use of multilingual education to build a convivialist society. The article reflects theoretically on how to combine convivialist education (Hétier and Wallenhorst, 2021) and multilingual education (Cummins, 1981;Skutnabb-Kangas, 2009).Today's hyperdiversity in society faces a dual challenge in accelerating and unsettling climate change. The convivialist manifesto (Convivialist International, 2020 a & b) entails five key principles namely: common naturality where humans are interdependent with nature; common humanity which must be respected in each person beyond any identity differences; common sociality, based on long-lasting and rich relationships in various human communities; legitimate individuation where the singularity of the person contributes to the common good; and eventually, creative opposition where conflicts are dealt in a fertile, peaceful and deliberative manner. These key principles are additionally subordinated to the need to control human desire for hubris and never-ending possession which represents a political alternative to material growth ideology (Convivialist International, 2020, a & b). The concept of intertwining convivialist education and multilingual education is illustrated through a case study [Master dissertation] in a Norwegian school context focussing on the significance of mother tongue education in the school curriculum for mitigating climate change (Manral, 2022). The data for the case study was gathered by conducting focus group discussions with three mother tongue teachers and two Norwegian language teachers working in a language school for newly arrived immigrant pupils in Norway. The findings identified the limitation of the Norwegian Education Act (1998, section 2-8), lacunas in the bilingual learning curricula and it argued for the need to strengthen mother tongue education and the role of mother tongue teachers in promoting sustainable development in the school curriculum (Manral, 2022).Based on the study's specific contextual findings and theoretical perspectives combining convivialist and multilingual education, the article infers that promoting multilingual education in schools can help mitigate climate change, and promote biocultural diversity (Brossard Børhaug, 2021, 2023;Maffi, 2018), and build a more convivialist society. The article thus aims to suggest some practical suggestions in a Norwegian plurilingual context and furthermore, it explores an expanded theoretical frame for convivialist multilingual education.